2019
DOI: 10.1093/geronb/gbz130
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation on Episodic Memory in Older Adults: A Meta-analysis

Abstract: Objectives In the last two decades, the number of intervention studies using transcranial direct current stimulation (tDCS) has grown enormously. Though some studies have shown positive influences on episodic memory among older adults, disagreement exists in the literature. Therefore, the current meta-analysis aimed to provide a quantitative assessment of the efficacy of tDCS in modulating episodic memory functions in older adults. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…However, some studies find no change in working memory for older adults following tDCS with n-back tasks 30 , 58 , which are in accordance with the present study’s findings in the tDCS-only condition. Inconsistent findings are also present when examining tDCS effects in other cognitive domains, which may be attributed to differences in stimulation parameters, such as current intensity, duration of stimulation, and stimulation site 59 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, some studies find no change in working memory for older adults following tDCS with n-back tasks 30 , 58 , which are in accordance with the present study’s findings in the tDCS-only condition. Inconsistent findings are also present when examining tDCS effects in other cognitive domains, which may be attributed to differences in stimulation parameters, such as current intensity, duration of stimulation, and stimulation site 59 .…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies have also found null effects after stimulation over the DLPFC 71 or temporoparietal cortex 72 , and even impaired associative memory after stimulation of the left inferior frontal gyrus 73 . Nonetheless, a meta-analysis showed that tDCS strengthened episodic memory for older adults with moderate effect sizes 59 . The null accuracy and RT effects on the auditory WRT add to this mixed pattern of findings, and may reflect some limitations in our experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sandrini et al (2020) reviewed the effects of tDCS on episodic memory in aging and concluded that one of the main limitations in this field is the lack of reliability. Thus, despite the growing body of work suggesting that brain stimulation techniques might be used to induce episodic memory improvements in aging ( Huo et al, 2019 ), many of the reported cognitive effects still need to be independently replicated and mechanistically elucidated ( Sandrini et al, 2020 ). One of the major factors underlying this lack of reliability is the observed individual variability in response to the various non-invasive brain stimulation (NIBS) protocols (i.e., López-Alonso et al, 2014 ; Wiethoff et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, a growing body of literature has described the role of atDCS in improving episodic memory, including both item and associative memory, in older adults [ 18 21 ]. According to the latest meta-analysis, older adults receiving atDCS showed memory improvements, with a significant and modest effect size (Hedges′ g = 0.625, [ 22 ]). Beneficial effects of atDCS on episodic memory may result from modify learning-related synaptic connections and then modulating brain functions.…”
Section: Introductionmentioning
confidence: 99%